Reducing income inequality in Europe - Anthony Barnes Atkinson (IZA Journal of European Labor Studies, 2013)
World leaders have come to recognise the challenge posed by high and rising economic inequality. This paper asks how Europe can address excessive inequality. It argues that we should learn from the lessons of history; there have been significant periods in the past when inequality fell. We can make use of economic analysis, drawing on both recent and older literatures. Inequality arises not only between skilled and unskilled workers, but also between labour and capital. In seeking solutions, we should go beyond the options currently prominent in public debate and be willing to think ?outside the box?.
Keywords: D31; J31; D63; 330; inequality wages capital redistribution